Advertising a Desired Change: When Process Simulation Fosters (vs. Hinders) Credibility and Persuasion - Cian, Luca; Longoni, Chiara; Krishna, Aradhna (Journal of Marketing Research, 2020)
Ads promising a desired change are ubiquitous in the marketplace. These ads typically include visuals of the starting and ending point of the promised change (“before/after” ads). “Progression” ads, which include intermediate steps in addition to starting and ending points, are much rarer in the marketplace. Across several consumer domains, the authors show an ad-type effect: progression ads foster spontaneous simulation of the process through which the change will happen, which makes these ads more credible and, in turn, more persuasive than before/after ads (Studies 1–3). The authors also show that impairing process simulation and high skepticism moderate the ad-type effect (Studies 4–5). Finally, they show effect reversals: if consumers focus on achieving the desired results quickly, and it is possible to do so, progression ads and the associated process simulation backfire in terms of credibility and persuasion (Studies 6–7). These findings contribute to existing research by identifying conditions under which progression ads have beneficial or disadvantageous effects. These findings have managerial implications because they run counter to current marketing practices, which favor before/after over progression ads.